Wind-tunnel model of Shoreham Nuclear Power Station, Unit I, Long Island Lighting Company, part II: progress report - Meroney, Robert N., author; Cermak, Jack E., author; Chaudhry, Fazal Hussain, author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1969)
Tests were conducted in a meteorological wind tunnel to determine the distribution of gas concentrations resulting from gaseous plumes released from isolated stacks and short stacks varying in height on top of a model of the Shoreham Nuclear Power Station reactor building. The tests were conducted over a reactor complex model which included downstream topography for a critical flow direction of 345 degrees from called north. Data obtained included photographs of model smoke plume trajectories, plume ground impingement distances shown by indicator paints, and local concentration of Kr-85 at the reactor station site boundary. The effects of an additional reactor building expansion were also measured.
CER68-69RNM-JEC-FHC14.
Shoreham Nuclear Powerplant (N.Y.).
Under contract to Stone and Webster Engineering Corporation, Boston (Mass.).
May 1969.
Keywords: Wind tunnel models; Buildings -- Aerodynamics